2022
DOI: 10.1111/wvn.12576
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of telemedicine interventions on women with postpartum depression: A systematic review and meta‐analysis

Abstract: Background Postpartum depression (PPD) is a public health problem that has significant adverse effects on mothers, couple's relationships, newborn neurodevelopment, and child emotional and cognitive development. This study reviewed the effectiveness of telemedicine interventions in postparturient women with postpartum depression. Aims To evaluate the effectiveness of telemedicine intervention in women with postpartum depression. Methods Cochrane Library, PubMed, EMBASE, Web of Science, CINAHL, and PsycINFO wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 63 publications
0
13
1
Order By: Relevance
“…As hypothesized, participants reported reductions in depression symptoms ( d = .93), parenting stress ( d = .63), anxiety ( d = .58), and infant internalizing problems ( d = .51). Compared to recent meta-analyses of studies testing interventions (traditional psychotherapy and telehealth) for maternal mental health in the postpartum period, our study found similar or slightly greater effect sizes in terms of reductions in depression and anxiety symptoms, infant internalizing problems, and parenting stress [ 75 77 ]. These findings are promising as maternal mental health in early childhood has important implications for child behaviour and executive functioning in later childhood [ 78 ].…”
Section: Discussioncontrasting
confidence: 43%
“…As hypothesized, participants reported reductions in depression symptoms ( d = .93), parenting stress ( d = .63), anxiety ( d = .58), and infant internalizing problems ( d = .51). Compared to recent meta-analyses of studies testing interventions (traditional psychotherapy and telehealth) for maternal mental health in the postpartum period, our study found similar or slightly greater effect sizes in terms of reductions in depression and anxiety symptoms, infant internalizing problems, and parenting stress [ 75 77 ]. These findings are promising as maternal mental health in early childhood has important implications for child behaviour and executive functioning in later childhood [ 78 ].…”
Section: Discussioncontrasting
confidence: 43%
“…Among the 12 meta-analyses, 11 were conducted with article quality evaluation and a description of the quality evaluation tool, and 1 study (Roman et al 2019 ) did not mention whether quality evaluation was performed. The quality evaluation tools for each of the 11 articles were as follows: 7 studies (Lau et al 2017 , 2020 , 2022 ; Liu et al 2022 ; Loughnan et al 2019 ; Neo et al 2022 ; Zhao et al 2021 ) used the Cochrane Risk of Bias tool (Higgins et al 2011 ), 1 study (Chae and Kim 2021 ) used the Cochrane Risk of Bias 2.0 (Sterne et al 2019 ), 2 studies (Nair et al 2018 ; Dol et al 2020 ) used the JBI (Lockwood et al 2015 ), and 1 study (Mu et al 2021 ) used the Jadad scale (Jadad et al 1996 ). GRADE (Guyatt et al 2008 ) was used to evaluate the evidence quality of four articles (Dol et al 2020 ; Lau et al 2020 , 2022 ; Neo et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…GRADE (Guyatt et al 2008 ) was used to evaluate the evidence quality of four articles (Dol et al 2020 ; Lau et al 2020 , 2022 ; Neo et al 2022 ). Almost all the included papers, except for three (Liu et al 2022 ; Nair et al 2018 ; Roman et al 2019 ), were supported by grants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It usually develops within the first 6 months after delivery (Iwata et al, 2016). Recent meta‐analyses revealed that the overall prevalence of postpartum depression is 17.7% globally (Hahn‐Holbrook et al, 2018) and 15% in China (Liu, Ma, & Yu, 2019). This condition can have far‐reaching adverse effects on the mother's physical and mental health, as well as her offspring's psychological health and cognitive and behavioural development (Bluett‐Duncan et al, 2021; Bo et al, 2021; Tainaka et al, 2022).…”
Section: Introductionmentioning
confidence: 99%